2018
DOI: 10.1523/jneurosci.0425-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency Response of Outer Hair Cell Voltage-Dependent Motility Is Limited by Kinetics of Prestin

Abstract: The voltage-dependent protein SLC26a5 (prestin) underlies outer hair cell electromotility (eM), which is responsible for cochlear amplification in mammals. The electrical signature of eM is a bell-shaped nonlinear capacitance (NLC), deriving from prestin sensor-charge (Q) movements, which peaks at the membrane voltage, V, where charge is distributed equally on either side of the membrane. Voltage dependencies of NLC and eM differ depending on interrogation frequency and intracellular chloride, revealing slow i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 54 publications
(45 reference statements)
0
85
1
Order By: Relevance
“…However, these data were obtained at voltage offsets far removed from V h , which has questionable physiological significance. Based on our measures (Santos-Sacchi and Tan, 2018), we estimate that their depolarized offset from V h would have been ∼65 mV. Indeed, by exploring at an offset potential near V h , we recently demonstrated that eM measured with the microchamber displays significant low-pass behavior (Santos-Sacchi and Tan, 2018).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…However, these data were obtained at voltage offsets far removed from V h , which has questionable physiological significance. Based on our measures (Santos-Sacchi and Tan, 2018), we estimate that their depolarized offset from V h would have been ∼65 mV. Indeed, by exploring at an offset potential near V h , we recently demonstrated that eM measured with the microchamber displays significant low-pass behavior (Santos-Sacchi and Tan, 2018).…”
Section: Introductionmentioning
confidence: 78%
“…As noted above, whole-cell NLC determination was made following stray capacitance removal (Santos-Sacchi et al, 1998; Santos-Sacchi and Song, 2016; Santos-Sacchi, 2018; Santos-Sacchi and Tan, 2018). Patch pipettes were coated with M-coat (Micro Measurements) to reduce stray capacitance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although delays for prestin-associated currents in vitro (Santos-Sacchi and Tan, 2018) are longer than the latency difference between the reticular lamina and basilar membrane vibration in vivo, they vary with the membrane voltage of outer hair cells. Voltage excitation away from the resting membrane potential has been shown to have a faster response.…”
Section: Discussionmentioning
confidence: 99%